A New Combination of Radio-Frequency Coil Configurations Using High-Permittivity Materials and Inductively Coupled Structures for Ultrahigh-Field Magnetic Resonance Imaging - Jeung-Hoon Seo; Young-Seung Jo; Chang-Hyun Oh; Jun-Young Chung (Sensors, 2022)
In ultrahigh-field (UHF) magnetic resonance imaging (MRI) system, the RF power required to excite the nuclei of the target object increases. As the strength of the main magnetic field (<semantics>B0</semantics> field) increases, the improvement of the RF transmit field (<semantics><msubsup>B1+</msubsup></semantics> field) efficiency and receive field (<semantics><msubsup>B1−</msubsup></semantics> field) sensitivity of radio-frequency (RF) coils is essential to reduce their specific absorption rate and power deposition in UHF MRI. To address these problems, we previously proposed a method to simultaneously improve the <semantics><msubsup>B1+</msubsup></semantics> field efficiency and <semantics><msubsup>B1−</msubsup></semantics> field sensitivity of 16-leg bandpass birdcage RF coils (BP-BC RF coils) by combining a multichannel wireless RF element (MCWE) and segmented cylindrical high-permittivity material (scHPM) comprising 16 elements in 7.0 T MRI. In this work, we further improved the performance of transmit/receive RF coils. A new combination of RF coil with wireless element and HPM was proposed by comparing the BP-BC RF coil with the MCWE and the scHPM proposed in the previous study and the multichannel RF coils with a birdcage RF coil-type wireless element (BCWE) and the scHPM proposed in this study. The proposed 16-ch RF coils with the BCWE and scHPM provided excellent <semantics><msubsup>B1+</msubsup></semantics> field efficiency and <semantics><msubsup>B1−</msubsup></semantics> field sensitivity improvement.